2011
DOI: 10.1242/dmm.006130
|View full text |Cite
|
Sign up to set email alerts
|

Development of severe skeletal defects in induced SHP-2-deficient adult mice: a model of skeletal malformation in humans with SHP-2 mutations

Abstract: SUMMARYSHP-2 (encoded by PTPN11) is a ubiquitously expressed protein tyrosine phosphatase required for signal transduction by multiple different cell surface receptors. Humans with germline SHP-2 mutations develop Noonan syndrome or LEOPARD syndrome, which are characterized by cardiovascular, neurological and skeletal abnormalities. To study how SHP-2 regulates tissue homeostasis in normal adults, we used a conditional SHP-2 mouse mutant in which loss of expression of SHP-2 was induced in multiple tissues in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 63 publications
(84 reference statements)
5
46
1
Order By: Relevance
“…Finally, our data do not exclude that other processes, independent of the GH/ IGF-1 axis, could be impaired in NS mice and result in growth retardation. Indeed, skeletal and growth abnormalities have been reported in inducible and neuronal-specific SHP2 knockout models (27,28). Further studies will be necessary to elucidate the part of those different mechanisms in NS-associated short stature.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our data do not exclude that other processes, independent of the GH/ IGF-1 axis, could be impaired in NS mice and result in growth retardation. Indeed, skeletal and growth abnormalities have been reported in inducible and neuronal-specific SHP2 knockout models (27,28). Further studies will be necessary to elucidate the part of those different mechanisms in NS-associated short stature.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ITIMbearing adaptor molecules are known to inhibit ITAM signaling via a recruitment of phosphatases such as SHP-1, SHP-2, and SHIP proteins. SHP-1 and SHIP-1 knock-out mice are reported to exhibit severe osteoporosis because of a dramatically increased number of osteoclasts (21,22). Because TLT-1s lacks the extracellular Ig domain compared with full-length TLT-1, we hypothesized that TLT-1s acts as a genuine adaptor molecule in a similar fashion with DAP12 and FcR␥ that are also deficient in the extracellular domain.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of NS, scoliosis and other spinal deformities are frequently encountered [49,50] and it was recently reported that NS children may have decreased bone mineralization [51], even though this study was performed on a limited number of patients. This hypothesis is also based on a recent report showing that PTPN11 disruption causes severe skeletal defects in mice [52]. Nonetheless the validity of this hypothesis has not been tested yet.…”
Section: Defects In Bone Homeostasismentioning
confidence: 99%